Identification and characterization of extrachromosomal circular DNA in Wei and Large White pigs by high-throughput sequencing - Wen, Aiyou; Zhang, Wei; Xu, Jingen; Wang, Kunping; Hu, Hong (Frontiers in Veterinary Science, 2023)
Wei pig (WP) and Large White pig (LP) are fatty and lean breeds, respectively. Extrachromosomal circular DNA (eccDNA) plays an important role in regulating signaling pathway processes of cell. However, there are few reports regarding the eccDNA and ecDNA profiles in WP and LP. The present work aimed to investigate the eccDNA and ecDNA profiles between WP and LP. Three WPs and three LPs (100±1.3 kg) were selected for analysis of eccDNA and ecDNA in the ear samples. Results showed that there were 39,686,953,656 ‒ 58,411,217,258 and 53,824,168,657 ‒ 58,311,810,737 clean data for WP and LP, respectively. Sequencing yielded 15,587–25,479 and 71,123–79,605 eccDNAs from the ear samples of WP and LP, respectively. There were 15,111 and 22,594 eccDNA-derived genes in the WP and LP, respectively, and 13,807 eccDNA-derived genes were common in the ear samples of both pigs. Sequencing yielded 13 – 19 and 27– 43 ecDNAs in the ears of WP and LP, respectively. There were 1,005 and 1,777 ecDNA-derived genes in WP and LP, respectively, and 351 ecDNA-derived genes were common in the ear samples of both pigs. The most significant KEGG pathways of eccDNA-derived genes were axon guidance, focal adhesion, metabolic pathways, MAPK signaling pathway, Hedgehog signaling pathway, microRNAs in cancer, tight junction, phospholipase D signaling pathway, endocytosis, and sphingolipid signaling pathway. Furthermore, the most significant KEGG pathways of ecDNA-derived genes were olfactory transduction, B cell receptor signaling pathway, and chemical carcinogenesis. The eccDNA00044301 was lower abundance, while the ecDNA00000060 was higher abundance in WP compared with that in LP. Summary, we found that eccDNAs and ecDNAs are common in WP and LP and occur in sizes large enough to carry one or several partial or complete genes. These findings have expanded the knowledge repertoire of circular DNA in pig and will provide a reference for the use of pigs as a medical model and help discovery of new genetic markers to select high-quality breeds.